PENGARUH PERTUMBUHAN EKONOMI DAN PENGELUARAN PEMERINTAH TERHADAP PENYERAPAN TENAGA KERJA SERTA KESEJAHTERAAN MASYARAKAT DI PROVINSI BALI - Pratiwi, Ni Putu Ambar; Indrajaya, I Gusti Bagus (Buletin Studi Ekonomi, 2019)
Abstract: The Effect of Economic Growth and Government Expenditures on Absorption of Labor and Public Welfare in the Province of Bali. This study aims to determine the condition of employment in the Province of Bali, analyzing the effect of economic growth and government expenditure on employment and community welfare. This data is obtained from the Central Statistics Agency of Bali province. The analysis technique used is Path Analysis. The results showed that economic growth had a positive and insignificant influence on the absorption of employment in the province of Bali and government expenditure had a positive and significant effect on employment in the Province of Bali. Government expenditure and employment have a positive and significant influence on the welfare of the people in Bali Province while economic growth has a non-significant effect on people’s welfare. Labor absorption mediate economic growth towards the welfare of the people in Bali Province while the absorption of labor does not mediate government spending on the welfare of the people in Bali Province in 2013-2017.